2023
DOI: 10.1186/s40001-023-01094-7
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of MMP-9, TIMP-1 and MMP-9/TIMP-1 ratio for diagnosis and assessment of COPD severity

Abstract: Background Inflammation, oxidative stress and an imbalance between proteases and protease inhibitors are recognized pathophysiological features of chronic obstructive pulmonary disease (COPD). The aim of this study was to evaluate serum levels of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in patients with COPD and to assess their relationship with lung function, symptom severity scores and recent acute exacerbations. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The changes in the functions of activated macrophages require further investigation. Matrix metalloproteinase 9 (MMP9) and transforming growth factor beta (TGF-β) were considered important hazardous cytokines in the pathogenesis of COPD, as they respectively participated in the processes of alveolar structure destruction and airway remodeling [ 42 44 ]. The RT-qPCR analysis found the elevated mRNA levels of TGFB1 and MMP9 in CM-treated THP-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the functions of activated macrophages require further investigation. Matrix metalloproteinase 9 (MMP9) and transforming growth factor beta (TGF-β) were considered important hazardous cytokines in the pathogenesis of COPD, as they respectively participated in the processes of alveolar structure destruction and airway remodeling [ 42 44 ]. The RT-qPCR analysis found the elevated mRNA levels of TGFB1 and MMP9 in CM-treated THP-1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings revealed that extracellular PCSK9 induces inflammatory cytokines and activates inflammatory pathways, suggesting that elevated levels of PCSK9 in BALF trigger inflammation in the airways and potentially contribute to inflammatory exacerbations in disease conditions. Role of MMP9 is implicated in fibrosis 29 and severity of COPD 30 . In our investigation, PCSK9-stimulated PBEC induced MMP9, suggesting a potential cause of tissue injury and exacerbation in COPD.…”
Section: Discussionmentioning
confidence: 99%